2022
DOI: 10.3390/ijerph192215034
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Corporate Green Financial Constraints: Evidence from China’s Listed Companies

Abstract: This paper aims to investigate how air pollution may affect corporate green financial constraints. We assume that poor air quality can enhance the pressure of governments on environmental protection, which creates easier access to financing for firms’ green investments and transitions, especially in emerging markets. Using a sample of Chinese-listed companies, we find that the level of green financial constraints is reduced when air quality deteriorates. This effect is more obvious in regions with stronger loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Zhang et al [35] observed that air pollution aggravates firms' information environment and financial constraints due to information asymmetry, resulting in significant underpricing during initial public offerings (IPOs). On the other hand, considering green finance and governmental intervention in environmental preservation, Shen et al [36] presented a contrasting perspective. They argued that acute air pollution exerts considerable environmental pressure on governments, prompting them to ease green financing thresholds for companies via green credit policies, thus aiding their ecological transition.…”
Section: H2(a) Air Pollution Leads To Increased Public Environmental ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [35] observed that air pollution aggravates firms' information environment and financial constraints due to information asymmetry, resulting in significant underpricing during initial public offerings (IPOs). On the other hand, considering green finance and governmental intervention in environmental preservation, Shen et al [36] presented a contrasting perspective. They argued that acute air pollution exerts considerable environmental pressure on governments, prompting them to ease green financing thresholds for companies via green credit policies, thus aiding their ecological transition.…”
Section: H2(a) Air Pollution Leads To Increased Public Environmental ...mentioning
confidence: 99%
“…(1) The government must focus on enhancing pollution control and treatment frameworks, solidifying the execution of the central environmental protection inspection mechanism, and continually improving industrial incentive schemes to cultivate an optimal environment for superior corporate growth. Given the local governments' augmented authority in China's political structure, which has inadvertently weakened the enforcement prowess of environmental agencies due to the territorial management approach [36], it is imperative to bolster the vertical management system of these bodies and the centralized inspection regime, thereby laying a strong legal groundwork for environmental stewardship. The government is also encouraged to optimize energy usage, advocate for efficient fossil fuel use, and support the advancement of clean, renewable energy sources.…”
Section: Conclusion 61 Conclusion and Implicationsmentioning
confidence: 99%
“…Under the influence of global sustainability agreements, such as the Kyoto Protocol, the energy industry faces increasing pressure on sustainable development (Chodnicka-Jaworska, 2022;Deng, et al, 2022;Shen, et al, 2022;Wanday and Ajour El Zein, 2022). Especially in recent China, with the introduction of national policies including "carbon peaking and carbon neutrality" (Ju, et al, 2022), Chinese energy firms face severe sustainability challenges.…”
Section: Introductionmentioning
confidence: 99%